Synthesis and biological evaluation of 1-amino isochromans from 2-bromoethyl benzaldehyde and amines in acid medium. Issue 2 (15th January 2018) - Fatima, Narjis; Reddy, B.V. Subba; Gowravaram, Sabitha; Yadav, J.S.; Kadari, Sudhakar; Putta, Chandra Shekar
Graphical abstract: Abstract: We have developed a facile and efficient synthetic route to substituted isochromans for the first time by reacting 2-(2-bromoethyl)benzaldehyde with a variety of aryl, heteroaryl amines in AcOH. The reaction is catalyst/additive free and takes place at reflux conditions with short reaction time to furnish products in good to excellent yields. All the compounds have been characterized by spectral techniques such as IR, 1 H NMR and Mass etc. Synthesized compounds were evaluated for antimicrobial activity against specific bacterial like 1) Staphylococcus strains aureus 2) Bacillus subtilis 3) Escherichia coli 4) Pseudomonas aeruginosa . Compounds3e, 3n, 3 m, 3 l, 3 k, 3j and3b showed most potent in vitro activity against bacterial strains.